Adrian Goldstone - Maurice Dunbar:::Creator::::::::::::; Hayman, Lee Richard (collector):::Contributor::::::::::::
Adrian Goldstone, prominent collector of Steinbeck books, in library of Maurice Dunbar, the photographer.